As coleções da Editora Globo de Porto Alegre : inovação e ineditismo (1930-1960) - Vieira, Júnia Cristina Vaz (2017)
This thesis aims at analyzing the collections of publishing house Editora Globo of Porto Alegre with regard to innovations in the Brazilian editorial market between 1930 and 1960. It focuses on its then unprecedented editorial choices, which appealed to both readers who love adventure and mystery literature, with its Coleção Amarela (Yellow Collection) and Coleção Universo (Universe Collection), and those avid to read classics and award-winning authors, published as Coleção Nobel (Nobel Collection) and Coleção Biblioteca dos Séculos. Other relevant aspects addressed in this thesis are the attention to the literary quality of the books published by Editora do Globo and the methodology utilized for the selection of titles for its catalog.